2007
DOI: 10.1007/s10551-006-9306-z
|View full text |Cite
|
Sign up to set email alerts
|

Ethics Programs, Perceived Corporate Social Responsibility and Job Satisfaction

Abstract: corporate social responsibility, job satisfaction, organizational ethics,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
378
3
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(412 citation statements)
references
References 66 publications
(81 reference statements)
22
378
3
9
Order By: Relevance
“…Valentine and Fleischman (2008) suggest that individuals prefer organizations that promote business ethics (Jose & Thibodeaux, 1999;Trevino, Butterfield, & McCabe 1998;Trevino & Nelson, 2004) and CSR is a natural extension of organizational ethics, which involves answering the requirements of stakeholders, with particular focus on societal issues and challenges. Thus, when an individual finds his/ her organization is involved in CSR, he/she feels good about his/her organization because of an enhanced self-image and delight, which ultimately leads to a higher sense of emotional attachment to the organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valentine and Fleischman (2008) suggest that individuals prefer organizations that promote business ethics (Jose & Thibodeaux, 1999;Trevino, Butterfield, & McCabe 1998;Trevino & Nelson, 2004) and CSR is a natural extension of organizational ethics, which involves answering the requirements of stakeholders, with particular focus on societal issues and challenges. Thus, when an individual finds his/ her organization is involved in CSR, he/she feels good about his/her organization because of an enhanced self-image and delight, which ultimately leads to a higher sense of emotional attachment to the organization.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between CSR and employee attitude and behavior, perhaps, cannot be considered as an under-researched area. Most of the published studies exploring perceived CSR and attitude of employees focused either on organizational commitment (OC) (Ali, Rehman, Ali, Yousaf, & Zia, 2010;Brammer, Millington, & Rayton, 2007;Dhanesh, 2010;Ebeid, 2010;Maignan & Ferrell 2001;Maignan, Ferrell, & Hult 1999;Peterson, 2004;Turker, 2009;You et al, 2013;Zheng 2010) or job satisfaction (Riordan, Gatewood, & Bill 1997;Tziner, Bar, Oren, & Kadosh, 2011;Valentine & Fleischman, 2008;You et al, 2013). However, with few exceptions (Ali et al, 2010, Zheng, 2010, most of the studies viewed them as dependent rather than mediating variables (Riordan, Gatewood, & Bill, 1997;Valentine & Fleischman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A well-established predictor of job satisfaction is the congruence between employees' work values and perceived opportunities to fulfill these values at their job, often described as needs-supply fit (e.g., Cable and DeRue 2002;Kristof-Brown et al 2005). Several studies have shown that CSR is positively related to employee satisfaction (see Ellemers et al 2011;Tziner et al 2011;Valentine and Fleischman 2008;Zhu et al 2014). This effect has been found to be particularly strong when employees perceive the CSR practice to reflect intrinsic organizational values rather than extrinsic promotionally driven motivations (Vlachos et al 2013).…”
Section: The Effects Of Csr On Employee Satisfactionmentioning
confidence: 99%
“…newly, the emphasis of CSR has shifted from one-sided profits orientation to many-sided social benefits (Valentine & Fleischman 2008). However, even though increasing attention has been given to CSR, a large amount of research had focused on stakeholders outside the corporation.…”
Section: 1-significance Of Studymentioning
confidence: 99%